Culturally responsive leadership in Malaysian small schools context : a preliminary survey - Mohd Norlizam Mohd Razali; Aida Hanim A. Hamid (Penerbit Universiti Kebangsaan Malaysia, 2022)
Principals and headteachers are leaders in schools. Various past studies showed that the leadership of school leaders may influence students’ achievement. These past studies demonstrated that the leaderships of school leaders also influence the actions and achievements of the teachers in schools. Thus, as stated in the fifth Malaysia Education Development Plan 2013-2025 (MOE, 2012), the Ministry of Education Malaysia (MOE) decided to place high-performing leaders in schools. This study discussed culturally responsive leadership. It examined the background, culturally related issues in Malaysia, and dimensions of culturally responsive leadership in the small school context in Malaysia based on past studies in external and domestic contexts related to culturally responsive leadership. This study was a preliminary survey that aimed at confirming the appropriateness of the dimensions found in the culturally responsive leadership framework introduced by Khalifa, Gooden, and Davis (2016) derived from the literature review. The data for this study was collected using semi-structured interviews involving two headteachers and two teachers from small schools. The findings from the interview were analysed and discussed further in this study, with the support of secondary data. In conclusion, the dimensions found in this framework are suitable as culturally responsive leadership practices in Malaysia and to be used as a basis in the implementation of further studies related to culturally responsive leadership in small schools in Malaysia.